2014
DOI: 10.1515/hf-2013-0132
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, thermal, and structural aspects of dried and redispersed nanofibrillated cellulose (NFC)

Abstract: The effects of various drying techniques, such as air, oven, freeze, and spray drying, on the morphological, thermal, and structural behaviors of two different nanofibrillated cellulose (NFC) materials were investigated. Field emission scanning electron microscopy (FE-SEM) observations indicated an interlaced network formation of predominantly in-plane fibrillar orientation for air-and oven-dried samples, while freeze and spray drying resulted in the formation of coarse and fine powder fractions. Comparison of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…All rheological investigations have shown that TEMPO-NFC hydrogels exhibit shear thinning and thixotropic behavior (Benhamou et al, 2014;Lasseuguette et al, 2008;Mendoza, Gunawardhana, Batchelor, & Garnier, 2018a;Mendoza et al, 2018b;Saito et al, 2007). Despite important reduction of particle swelling ability and suspension viscoelasticity that have been observed when nanocelluloses of different types were dried and re-dispersed in water (Hubbe et al, 2017;Naderi, Lindström, Sundstrom, & Flodberg, 2015a;Okiyama, Motoki, & Yamanaka, 1993;Peng, Gardner, & Han, 2012;Voronova, Zakharov, Kuznetsov, & Surov, 2012;Zepic et al, 2014;Zimmermann et al, 2016), the accessibility of dried nanocellulose offers potentials for novel TEMPO-NFC hydrogel blends and applications. In our previous publication (Šebenik, Krajnc, Alič, & Lapasin, 2018), development of rheological properties of hydrogels prepared from a commercially available freeze-dried TEMPO-NFC powder was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…All rheological investigations have shown that TEMPO-NFC hydrogels exhibit shear thinning and thixotropic behavior (Benhamou et al, 2014;Lasseuguette et al, 2008;Mendoza, Gunawardhana, Batchelor, & Garnier, 2018a;Mendoza et al, 2018b;Saito et al, 2007). Despite important reduction of particle swelling ability and suspension viscoelasticity that have been observed when nanocelluloses of different types were dried and re-dispersed in water (Hubbe et al, 2017;Naderi, Lindström, Sundstrom, & Flodberg, 2015a;Okiyama, Motoki, & Yamanaka, 1993;Peng, Gardner, & Han, 2012;Voronova, Zakharov, Kuznetsov, & Surov, 2012;Zepic et al, 2014;Zimmermann et al, 2016), the accessibility of dried nanocellulose offers potentials for novel TEMPO-NFC hydrogel blends and applications. In our previous publication (Šebenik, Krajnc, Alič, & Lapasin, 2018), development of rheological properties of hydrogels prepared from a commercially available freeze-dried TEMPO-NFC powder was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…wound healing applications. Previous studies have mainly focused on the evaluation of redispersibility and rheological properties of dilute 0.5 -1% NFC suspensions after spray drying or freeze-drying (Missoum, et al 2012;Žepič, et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in many studies that aqueous suspensions of MFC/NFC are highly shear thinning and show gel-like properties, especially at increased concentrations (Herrick et al 1983;Pääkko et al 2007;Agoda-Tandjawa et al 2010;Rezayati Charani et al 2013;Saarikoski et al 2015;Žepic et al 2014). The rheology of a high consistency furnish that contains large amount of MFC/NFC together with fillers and cellulose fibers was also observed to be governed by the swelling and gel-like properties of the MFC/NFC, as described by Dimic-Misic et al (2013).…”
Section: Introductionmentioning
confidence: 99%